Circulating memory B cells and plasmablasts are associated with the levels of serum immunoglobulin in patients with ulcerative colitis. Issue 5 (22nd January 2016) - Wang, Xinrui; Jiang, Yanfang; Zhu, Yonggang; Zhang, Manli; Li, Man; Wang, Hongjuan; Gao, Pujun
Abstract: Humoural immunity is crucial for the pathogenesis of ulcerative colitis (UC), but the precise perturbation of B cell immunity is poorly understood. This study is aimed at evaluating the numbers of different subsets of circulating memory B cells, plasmablasts, and the levels of serum immunoglobulin in UC patients. Total of 23 patients with active UC and 14 healthy controls (HC) were examined for the numbers of different subsets of circulating memory B cells and plasmablasts before and after treatment with mesalazine for 8–12 weeks by flow cytometry. Disease activity was evaluated by the Mayo clinic score. The levels of serum immunoglobulin, C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were measured in individual subjects. In comparison with that in HC, significantly reduced numbers of IgG +  IgD −  CD27 +  CD19 + memory B cells, increased numbers of CD20 −  CD19 + plasmablast subsets, and higher serum IgG levels were detected in UC patients. The concentrations of serum IgG, the numbers of CD138 +  CD38 +  CD20 −  CD19 +, and IgG +  CD38 +  CD20 −  CD19 + plasmablasts were negatively associated with the numbers of IgG +  IgD −  CD27 +  CD19 + memory B cells. Furthermore, the values of Mayo clinic score, CRP, or ESR in UC patients were negatively correlated with the numbers of IgG +  IgD −  CD27 +  CD19 + memory B cells, while positively correlated with the serum IgG levels and the numbers of plasmablast subsets. Following treatment with mesalazine, the numbers of circulating IgG +  IgD −  CD27 +  CD19 + memory B cells were significantly increased, while the numbers of CD138 +  CD38 +  CD20 −  CD19 + and IgG +  CD38 +  CD20 −  CD19 + plasmablasts were reduced in UC patients. These decreased IgG +  IgD −  CD27 +  CD19 + memory B cells and increased plasmablasts may be involved in the pathogenic process of UC.